From Ghent to Aix: How They Brought the News in the Habsburg Netherlands, 1550–1700 - Arblaster, Paul (Library of the Written Word, 2014)
Exploring the early decades of print journalism in the cities at Northern Europe's information crossroads, From Ghent to Aix reveals how news of war, diplomacy and politics travelled, and how political and commercial imperatives shaped the ways it was presented.